Assam land and people - Gopalkrishnan, R (New Delhi Omsons, 2000)
This book, Assam-land and people, represents reflections on basic attributes of the state and its society. It expresses personal views, interpretation and understanding, puts forth a case to argue. Above all,it is an attempt to place the contemporary inst
Keywords: Assam-Geography and maps; Geology, Economic; Economic development; Agriculture; Population